2022
DOI: 10.21203/rs.3.rs-1690952/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal and neonatal outcomes of assisted reproductive technology versus unassisted pregnancy: A propensity score-matched analysis

Abstract: Background: Assisted reproductive technology (ART) is generally safe, but still associated with risks of various adverse maternal and neonatal outcomes.Methods: This retrospective cohort study included all deliveries (through either ART or unassisted pregnancy) during a period from January 5th, 2015 to September 30th, 2020 at the Obstetrics and Gynecology Hospital of Fudan University, Shanghai, China. A propensity score-matched (PSM) analysis was conducted to compare adverse maternal and neonatal outcomes betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…13 While there is an obvious need in the Southwest, the need for Spanishspeaking physicians is present throughout the country. 1 By 2005, less than half of medical schools were providing any instruction on medical Spanish. 14 A survey published last year showed that among medical schools participating in the survey, 78% offered medical Spanish.…”
Section: Need For Spanish Language Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 While there is an obvious need in the Southwest, the need for Spanishspeaking physicians is present throughout the country. 1 By 2005, less than half of medical schools were providing any instruction on medical Spanish. 14 A survey published last year showed that among medical schools participating in the survey, 78% offered medical Spanish.…”
Section: Need For Spanish Language Skillsmentioning
confidence: 99%
“…Spanish is the most common non-English language spoken in the USA. 1 The USA also has the second largest population of Spanish speakers in the world after Mexico. 2 Native Spanish speakers experience barriers to healthcare and are known to be medically underserved.…”
Section: Need For Spanish Language Skillsmentioning
confidence: 99%
See 1 more Smart Citation